Hydration characteristic of mirha in normal and foamed concretes - Adilah Binti Mohd Zawawi, Adilah (2010)
Rice husk become one of the demanding waste problem since it is the byproducts of paddy milling industries. This by-product is actually contain amorphous silica after undergoes controlled burning process.